Chemomechanical oscillations with a non-redox non-oscillatory reaction. Issue 36 (20th April 2017) - Horváth, J.
Abstract : Periodic length changes, over 20%, were sustained in a pH-responsive gel by associating the methylene glycol–sulphite OH-producing clock-reaction with variations of the exchange time induced between the core of the gel and a steady chemical environment. Abstract : Periodic length changes, over 20%, were sustained in a pH-responsive gel by associating the methylene glycol–sulphite OH-producing clock-reaction with variations of the exchange time induced between the core of the gel and a steady chemical environment. This is the first synergistic actuator that operates beyond acid-producing redox reactions.